Bioactive components and potential mechanisms of Biqi Capsule in the treatment of osteoarthritis: based on chondroprotective and anti-inflammatory activity - Jia, Ziyue; Zhang, Jiale; Yang, Xintong; Chen, Huiyou; Wang, Yuxing; Francis, Opoku Bonsu; Li, Yuanchao; Liu, Zhanbiao; Zhang, Shaozhuo; Wang, Qilong (Frontiers in Pharmacology, 2024)
Cartilage damage and synovial inflammation are vital pathological changes in osteoarthritis (OA). Biqi Capsule, a traditional Chinese medicine formula used for the clinical treatment of arthritis in China, yields advantages in attenuating OA progression. The drawback here is that the bioactive components and pharmacological mechanisms by which Biqi Capsule exerts its anti-inflammatory and chondroprotective effects have yet to be fully clarified. For in vivo studies, a papain-induced OA rat model was established to explore the pharmacological effects and potential mechanisms of Biqi Capsule against OA. Biqi Capsule alleviated articular cartilage degeneration and chondrocyte damage in OA rats and inhibited the phosphorylation of NF-κB and the expression of pro-inflammatory cytokines in synovial tissue. Network pharmacology analysis suggested that the primary biological processes regulated by Biqi Capsule are inflammation and oxidative stress, and the critical pathway regulated is the PI3K/AKT signaling pathway. The result of this analysis was later verified on SW1353 cells. The in vitro studies demonstrated that Glycyrrhizic Acid and Liquiritin in Biqi Capsule attenuated H2O2-stimulated SW1353 chondrocyte damage via activation of PI3K/AKT/mTOR pathway. Moreover, Biqi Capsule alleviated inflammatory responses in LPS-stimulated RAW264.7 macrophages via the NF-κB/IL-6 pathway. These observations were suggested to have been facilitated by Brucine, Liquiritin, Salvianolic Acid B, Glycyrrhizic Acid, Cryptotanshinone, and Tanshinone ⅡA. Put together, this study partially clarifies the pharmacological mechanisms and the bioactive components of Biqi capsules against OA and suggests that it is a promising therapeutic option for the treatment of OA.